2017
DOI: 10.1016/j.cej.2017.03.047
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of photoelectrocatalytic degradation of diclofenac with persulfate activated by Cu cathode

Abstract: h i g h l i g h t s Photoelectro-oxidation of diclofenac was largely enhanced with persulfate addition. Cu 2 O was identified at copper cathode by in situ Raman technique. Activation mechanism of persulfate to SO 4 ÅÀ at copper cathode was proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(16 citation statements)
references
References 50 publications
2
13
0
1
Order By: Relevance
“…The study conducted by Wang and Bai (2017) found that in ozonation process which is an efficient oxidation process for degradation of pesticides, the formation of OH• by Fe-based catalysts can improve O3 decomposition. These findings were in alignment with the study by Liu, Zhao et al (2017) According to t -HCH was the most persistent pesticide in the reactor while the four other pesticides could -HCH, pentachlorobenzene, alachlor, diuron, and isoproturon were 64.8, 94.5, 97, 96.9 and 91.6%, respectively. In another study, the bimetallic silver/copper nanoparticles using Carica papaya (Ag/Cu-papaya) were synthesized by Rosbero and Camacho (2017) for chlorpyrifos removal from synthetic wastewater.…”
Section: Removal Of Pesticides By Advanced Oxidation Processes (Aops)supporting
confidence: 90%
“…The study conducted by Wang and Bai (2017) found that in ozonation process which is an efficient oxidation process for degradation of pesticides, the formation of OH• by Fe-based catalysts can improve O3 decomposition. These findings were in alignment with the study by Liu, Zhao et al (2017) According to t -HCH was the most persistent pesticide in the reactor while the four other pesticides could -HCH, pentachlorobenzene, alachlor, diuron, and isoproturon were 64.8, 94.5, 97, 96.9 and 91.6%, respectively. In another study, the bimetallic silver/copper nanoparticles using Carica papaya (Ag/Cu-papaya) were synthesized by Rosbero and Camacho (2017) for chlorpyrifos removal from synthetic wastewater.…”
Section: Removal Of Pesticides By Advanced Oxidation Processes (Aops)supporting
confidence: 90%
“…Phenylacetic acid structure on DCF might be attacked by SO 4 c À resulting in the transfer of an electron from aromatic ring to sulfate radical, and subsequently a -COOH group could be removed from this structure via intramolecular electron transfer producing a decarboxylation product m/z 252 (2-(2 0 ,6 0 -dichlorphenylamino)methylbenzene). 48 This product was also detected by Zhao et al 49 and Liu et al 50 in DCF degradation using ferrate(VI) and photoelectrocatalytic system, respectively. (iii) Formylation (pathway (3) in Scheme 1) might result from the oxidation of the methyl group in the product m/z 252 leading to the formation of the product m/z 266 (2-(2 0 ,6 0 -dichlorophenylamino)benzaldehyde).…”
Section: Degradation Mechanism Of Dcf By Hapmentioning
confidence: 57%
“…Shan has studied the degradation of DCF in a Fenton like system, FeCeO x -H 2 O 2 in detail, and the reaction rate constant of DCF degradation was 0.073 min −1 [48]. Liu has found that the rate constant of DCF (initial concentration was 10 mg L −1 ) degradation was 1.0498 h −1 in a Bi 2 MoO 6 /Cu/PEC/PS system [49]. Horiya has reported the degradation of DCF (the initial concentration was 10 mg L −1 ) with mont-La(6%)-Cu 0.6 Cd 0.4 S under NUV-Vis irradiation, and the removal of DCF was ca.…”
Section: Photocatalytic Activity Of the Ag 3 Po 4 /G-c 3 N 4 Compositesmentioning
confidence: 99%